Sosialisasi Pengolahan Air Sumur Bor Menjadi Bersih dengan Tray Aerator Ventury - Yerizam, Muhammad; Junaidi, Robert; Manggala, Agus; Riansyah, Epan; Tamara, Ade; Khairunnisa, Annisa Septia (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aimed to socialize the method of processing drilled well water into clean water that is suitable for use as boiler feed water, with a focus on the use of Tray Aerator Venturi tools to improve water quality. Methodology: The method applied was socialization and application of the Tray Aerator Venturi tool using 3D visualization, which was carried out directly at PT Utama Karya Techindo. The activity begins with a site survey, followed by discussions with company management to identify problems. Results: The results of this activity showed an increase in the understanding of PT Utama Karya Techindo staff regarding the water treatment process. The use of the Tray Aerator Venturi is effective in reducing the levels of iron (Fe) and manganese (Mn) in well water, which were previously the main causes of corrosion in boiler pipes. Conclusions: Using the Tray Aerator Venturi is effective and economical for processing well water into quality boiler feed water. Apart from improving water quality, this technology also reduces the risk of corrosion in pipes. This activity succeeded in providing understanding and skills to partners to operate and maintain the water treatment systems independently. Limitations: The lack of money available to manufacture Venture Tray Aerator tools to be implemented directly in companies to be more effective in outreach. Contribution: The outreach can be used for PT Utama Karya Techindo's needs in managing boiler feed water in Tanjung Enim. This service can be used for household needs in managing clean water because the equipment is easy to make and affordable.